Entrepreneurship-Based Strategies for Developing Superior Islamic Boarding Schools - Abdi, Muhammad Iwan; Sabran, Sabran (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines strategies to enhance the excellence of Islamic boarding schools by integrating entrepreneurship within the Islamic Education Foundation. This study focuses on the role of Trubus Business Center (TSB) as the main driver in creating an independent, adaptive, and superior pesantren ecosystem. Using a qualitative approach with case study methods, data were collected through interviews, observations, and institutional documentation. The results of the study show that three main strategies are carried out integratively, namely: (1) development planning based on local potential through the optimization of waqf land and productive business units; (2) improving the quality of teachers and education personnel through selective recruitment, continuous professional development, and empowerment in the management of pesantren businesses; and (3) the provision of adequate educational facilities and infrastructure, which is directly supported by the results of pesantren business units. These three strategies not only support the financial sustainability of the institution but also strengthen the academic, spiritual, and character dimensions of students holistically. These findings make a conceptual contribution to the development of a model of superior pesantren based on entrepreneurship and sustainable management that is contextual with local needs.